Development and characterization of microsatellite markers in sawih tree (Duabanga moluccana Blume) using ISSR-suppression PCR techniques. - Liew, Kit-Siong; Ho, Wei-Seng; Pang, Shek-Ling; Abdullah, Julaihi (Springer, 2015)
Duabanga moluccana(or locally known as sawih)is an indigenous fast growing tropical tree species that confersvarious advantages for the timber industry and for plantedforests development. In this paper, we isolated and characterized8 polymorphic microsatellite markers from theD. moluccanagenome using ISSR-suppression PCR techniques. The numberof alleles and PIC values ranged from 3 to 8 alleles per locus andfrom 0.488 to 0.792, respectively. Three microsatellite loci weredeviated from Hardy-Weinberg equilibrium (P<0.05). Thetransferability rate ranged from 24 to 100 % among the threeindigenous tree species tested. This indicates that the newlydeveloped microsatellite markers would be useful tools forpopulation genetic studies onD. moluccanaand otherindigenous tree species.